Sticky information and determinacy - Alexander Meyer-Gohde (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
The infinite-dimensional sticky-information Phillips curve is cast as a finite-dimensional timevarying system of difference equations in order to directly assess determinacy in the model with demand given by the forward-looking IS equation and monetary policy by an interest rate rule. An equivalence to the model without lagged expectations holds (albeit tenuously) for the particular specification and a common truncation method produces spurious determinacy.
Keywords: C62; E31; E43; E52; 330; determinacy; Taylor rule; sticky Information; time-varying difference equations; Phillips-Kurve; Unvollkommene Information; Dynamisches Gleichgewicht; Analysis; Taylor-Regel; Theorie